Peran Strategi Marketing Public Relation dalam Meningkatkan Citra Perusahaan (Studi Kasus Pada PT Intinusa Salareksa Tbk) - Rafli Cahyadi; Lukman . (CV. ITTC INDONESIA, 2026)
Corporate image is a strategic asset that plays an important role in building public trust and enhancing a company’s competitiveness. One communication approach used to develop a positive corporate image is Marketing Public Relations (MPR), which integrates marketing and public relations functions. This study aims to analyze the role of Marketing Public Relations strategies in improving the corporate image of PT Intinusa Salareksa Tbk. This research employs a qualitative approach using a case study method. Data were collected through in-depth interviews, observation, and documentation, while data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that Marketing Public Relations strategies significantly contribute to building a positive corporate image. Activities such as corporate publications, communication with business partners, implementation of Corporate Social Responsibility (CSR) programs, and the use of social media help shape public perceptions of the company’s professionalism, credibility, and social responsibility. These strategies are also aligned with the AIDA theory in attracting attention and fostering public trust. However, the study finds that two-way digital communication still needs to be strengthened to ensure a more optimal and sustainable corporate image development.